Design of Eddy Current Braking Test Stand for High-speed Maglev Train - Yijing XU; Haitao ZHAO; Wenjie XIA; Jiachuan GUO (机车电传动)
The system scheme of eddy current braking test-bed was designed to study the influencing factors of eddy current braking, and the functions of each module of the system were briefly introduced. The mechanical system of the test-bed was elaborated, and the size of the track wheel, the power of the motor and the moment of inertia of the test-bed were determined. Finally, the eddy current braking force of the test-bed was calculated theoretically and simulatedly, and compared with the measured data of the high-speed maglev train eddy current braking, which showed that the error between the three is very small.